2015
DOI: 10.2169/internalmedicine.54.4343
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Lupus Nephritis with High Titers of Myeloperoxidase Anti-Neutrophil Cytoplasmic Antibodies Using Tacrolimus

Abstract: A 63-year-old Japanese woman with a 30-year history of systemic lupus erythematosus developed macrohematuria and massive proteinuria after seroconversion of myeloperoxidase anti-neutrophil cytoplasmic antibodies (MPO-ANCA). A renal biopsy indicated focal proliferative lupus nephritis (class III A/C) with a fibrous crescent formation. Methylprednisolone pulse therapy (500 mg, 3 successive days) was administered because of progressive proteinuria. Steroid therapy did not suppress the progressive proteinuria; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Some studies reported that photosensitivity, oral ulcerations, and alopecia were more common in the ANCApositive group than in the ANCA-negative group [11], and others observed a higher remission rate and better prognoses when using mycophenolate mofetil (MMF) than when using cyclophosphamide as induction therapy for ANCA-positive LN patients. It was also reported that tacrolimus might be a useful immunosuppressant for patients with progressive LN and MPO-ANCAs [13,20]. The above results suggest that a preference for tacrolimus or MMF is indicated during drug selection for ANCA-positive patients.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Some studies reported that photosensitivity, oral ulcerations, and alopecia were more common in the ANCApositive group than in the ANCA-negative group [11], and others observed a higher remission rate and better prognoses when using mycophenolate mofetil (MMF) than when using cyclophosphamide as induction therapy for ANCA-positive LN patients. It was also reported that tacrolimus might be a useful immunosuppressant for patients with progressive LN and MPO-ANCAs [13,20]. The above results suggest that a preference for tacrolimus or MMF is indicated during drug selection for ANCA-positive patients.…”
Section: Discussionmentioning
confidence: 72%
“…The neutrophil-tolymphocyte ratio, ANCAs and the estimated glomerular filtration rate (EGFR) were reported to be independent risk factors for patient survival in another article [11]. Other studies also reported poor prognoses with increased ANCA values [13,18]. Among the results of the above studies, the CI is an index of renal biopsy, demonstrating the necessity of renal biopsy in LN.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is important to note that ANCA in LN is associated with higher SLE disease activity index score [7], worse renal function [6, 7], hypocomplementemia [46], dsDNA Ab [2, 6], and worse renal outcome [2, 4], as was exemplified in our case. Histologically, nearly 90% of such cases have been reported in association with class III or IV LN (Table 1) [2, 47, 1018]. In particular, ANCA positivity appears to be associated with higher incidence of class IV-S LN but lower incidence of class V LN, as well as endocapillary hypercellularity [6].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, renal biopsy is often used to diagnose AAV-related renal injury and evaluate the prognosis. But high-sensitivity and high-specificity markers for early diagnosis and prognosis evaluation would be preferable due to the invasive nature of the renal biopsy procedure ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%